Técnicas de análise de investimentos aplicadas à gestão de custos em projetos direcionados pelo prazo - Kawabuchi, Eduardo Noboru (2013)
The use of financial mathematics in project management usually is confined to preproject activities, being part of technical and economic feasibility atudy. After the start of the implementation of the project, it was found that the cost management is accomplished without further considers that a monetary unit does not have the same financial value on different dates. The existing literature on the project cost management does not address the issue. With this, is not established a direct relationship between the duration and costs of the Project, which is not true. A delay in any delivery of the project may not only reflect a negative result, it could mean a financial gain to the Project as a whole, at the same time that advances in deliveries may not always reflect only a positive result, it may adversely affect the financial result of the Project. This paper proposes a methodology the complement the traditional project cost management, integrated with capital budgeting practices in order to provide information that give support to decision making aimed at maximizing the return on investment